Globalna Północ i Globalne Południe w dyskursie edukacyjnym. Krytyczna analiza treści podręczników szkolnych - Popow, Monika (Wydawnictwo Naukowe UAM, 2015)
The aim of my paper is to analyze the representations of Global North and Global South, presented in geography textbooks in grammar school. First, the concept of global education is presented. Subsequently, representations of North and South and its inhabitants are reconstructed and analyzed. The method used is that of critical discourse analysis. Simultaneously, meanings of reconstructed representations are interpreted in a broad social and cultural context.
Global North and South in Educational Discourse. Critical Analysis of School Textbooks Content
Keywords: global education; critical discourse analysis; geography; textbooks